Flexible nano thermal insulation material and preparation method and application thereof

By using a combination of fibrotic adhesive and low thermal conductivity powder, a fiber network is formed, which solves the problems of insufficient mechanical properties of nano-insulating materials and easy dust peeling, and realizes the preparation of low-cost and high-performance flexible nano-insulating materials, suitable for High temperature application.

CN119241969AActive Publication Date: 2025-01-03TSINGHUA UNIVERSITY

Patent Information

Application Number
CN202410980760.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-01-03
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

Existing nano-insulating materials have problems such as insufficient mechanical properties, easy dust to fall off and high production costs, especially in high temperature environments, which are difficult to meet application needs.

Method used

Flexible nano-insulating materials are prepared by mixing fibrotic adhesive with low thermal conductivity powder, forming a fiber network through ball milling and rolling, which avoids the use of solvents and sintering process, simplifies the process and improves the flexibility and density of the material. .

Benefits of technology

It has achieved the preparation of high-performance flexible nano-insulating materials with low cost, with excellent flexibility, thermal insulation and certain tensile and compression properties. It is suitable for high-temperature scenarios and avoids the problems of dust shedding and insufficient mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a flexible nano thermal insulation material and a preparation method and application thereof, and the preparation method of the flexible nano thermal insulation material comprises the following steps: mixing low-heat-conductivity-coefficient powder, a fibrosis adhesive and an optional additive, carrying out ball milling to obtain floccule, and rolling the floccule into a film-shaped flexible nano thermal insulation material. According to the invention, the low-thermal-conductivity powder is cross-linked, fixed and rolled to form the flexible film by using the fibril formed by the fibrillating adhesive, so that the pore structure of the low-thermal-conductivity powder is maintained without introducing the adhesive with high thermal conductivity for forming; therefore, the low heat conductivity coefficient of the powder is kept, and meanwhile, the powder has good processing formability. The prepared flexible nano heat insulation material has excellent flexibility, heat insulation performance and certain tensile and compression performance, and can be widely applied to the fields of aerospace, constructional engineering, shipbuilding, automobile manufacturing and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal insulation materials, and in particular to a flexible nano thermal insulation material and a preparation method and application thereof. Background Art

[0002] At present, for thermal insulation materials, nano-insulation materials usually have the advantages of light weight, high temperature resistance, high porosity and ultra-low thermal conductivity because the pore size is smaller than the mean free path of air molecules (≤70nm). It is an ideal thermal insulation material and is widely used in aerospace, national defense, chemical industry, metallurgy, electric power, transportation and other fields.

[0003] Nano thermal insulation materials can be divided into aerogel thermal insulation materials and nano powder-based composite thermal insulation materials. Aerogel is a gel material with gas as the dispersion medium. It has ultra-light weight, low refractive index, low elastic modulus and ultra-low apparent thermal conductivity. However, the preparation cost of its molded blocks is high, the process is complex, the preparation cycle is long, and there is a problem of high brittleness. It usually needs to be compounded with fiber materials to enhance the mechanical properties. For example, the ceramic fiber felt composite silica aerogel composite material published by Aspen Aerogels Inc. in U.S. Patents 7078359B2, 6989132B2, 7399439B2, 7780890B2, 9181486B2, etc. has a room temperature thermal conductivity as low as 0.014W / (m·K). Chinese patent CN117303381B discloses a green preparation process of silica aerogel, and CN117779446A discloses a method for preparing a fireproof and heat-insulating aerogel gasket with high compressive strength for power battery cells, but the prepared nano-aerogel composite insulation material has the disadvantages of dust shedding and large brittleness of composite felt. In order to solve this pain point, researchers use coating encapsulation to solve the problem, but this also increases the complexity and cost of the preparation process. For example, Gongyi Fanrui Yihui Composite Materials Co., Ltd. has developed a pre-oxidized silk aerogel felt encapsulated with a coating, which solves the problems of dust shedding and felt brittleness, but the pre-oxidized silk aerogel felt has insufficient temperature resistance and is not suitable for application in high temperature environments. CN118308008A discloses a packaging coating for fireproof and heat-insulating aerogel gaskets for power battery cells and its application. The use of alicyclic epoxy fire retardant coating to encapsulate aerogel insulation gaskets can make ceramic fiber aerogel gaskets have better low-temperature flexibility, prevent dust shedding, and have sufficient flame retardancy and high temperature resistance. However, the manufacturing process of high-quality silica aerogel composite materials requires the use of CO2 supercritical drying equipment, which requires large fixed asset investment and high manufacturing costs.

[0004] Nano powder-based composite insulation materials are made by adding reinforcing materials, adhesives and other additives to nano silica aerogel powder or fumed silica powder as the base material under dry conditions, and then pressing and molding. The materials obtained by pressing and molding are usually high in density and poor in flexibility, which limits their practical applications. At the same time, such materials require further high-temperature sintering to eliminate the influence of adhesives. For example, Johns-Manville of the United States disclosed in U.S. Patent No. 2811457 that silica aerogel powder or fumed silica powder, metal zirconium powder, asbestos and phenolic resin are used as raw materials, mixed evenly and sintered at 650°C to obtain high-efficiency insulation materials. Johns-Manville registered the min-K® trademark for this material. The U.S. Atomic Energy Commission disclosed the formula and process of optimized min-K® materials in U.S. Patent No. 3634563, which uses fumed silica, rutile titanium dioxide or silicon carbide sunscreen, and chopped inorganic fibers as raw materials, which are mixed, pulped after adding ethyl acetate and octanoic acid, pressed and formed after the solvent evaporates, and then sintered at 900°C to obtain a lightweight porous nano thermal insulation material. CN118061611A and CN112140659A disclose flexible nano thermal insulation felts and preparation methods thereof. The flexible nano thermal insulation felts obtained by multi-layer sewing process contain hydrophilic fumed silica, micron-sized silicon carbide or titanium dioxide infrared sunscreens, and chopped glass fibers or ceramic fibers that play a toughening role. However, this type of material still has the problems of dust shedding and high brittleness of the board.

[0005] In order to solve the shortcomings of traditional nano thermal insulation materials, such as insufficient mechanical properties, easy dust shedding, and high manufacturing costs, it is necessary to find a new method for preparing nano thermal insulation materials to prepare nano thermal insulation materials that are intrinsically flexible and free of dust shedding. The present invention proposes a method for preparing flexible nano porous thermal insulation materials based on a fiberizable adhesive to bond low thermal conductivity powders, using a fiber network formed by an adhesive to form powders. The overall preparation process is simple and easy to mass produce, and overcomes the problems of poor mechanical properties and easy dust shedding of traditional materials. Summary of the invention

[0006] The present invention provides a flexible nano thermal insulation material and a preparation method and application thereof, so as to solve the defects of the prior art nano thermal insulation material such as easy shedding of dust, insufficient mechanical properties or high preparation cost, and realize low-cost preparation of high-performance flexible nano thermal insulation material.

[0007] In a first aspect, the present invention provides a method for preparing a flexible nano thermal insulation material, comprising: mixing a low thermal conductivity powder, a fiberizable adhesive and an optional additive, ball milling to obtain flocs, and rolling the flocs to form the flexible nano thermal insulation material in a film form.

[0008] The present invention uses the fiber network formed by the fiberizable adhesive during the ball milling process to bond the accumulated low thermal conductivity material powder, and forms a flexible film under the action of roller pressing. Since the main component material of the flexible film is the low thermal conductivity powder, the molding process will not destroy the pore structure of the low thermal conductivity powder itself, thereby maintaining the low thermal conductivity of the powder material itself; at the same time, the adhesive exists in the form of nano-scale fibers, which will not block the pore structure and therefore does not need to be sintered and removed. This preparation process does not require any solvent to assist, the preparation process is simple, and the shape of the product after molding is highly plastic, and the resulting product does not have the problem of easy dust shedding and insufficient mechanical properties.

[0009] Furthermore, the mass proportion of the low thermal conductivity powder is 85% to 95%, and the mass proportion of the fiberizable adhesive is 1% to 10%. The flexible nano thermal insulation material of the present invention uses the low thermal conductivity powder as the main component, and the amount of the fiberizable adhesive is based on the ability to bond the low thermal conductivity powder.

[0010] In the present invention, the low thermal conductivity powder is selected from fumed silica powder, silica aerogel powder, alumina aerogel powder, zirconia aerogel powder, vermiculite powder, perlite powder, nano carbon black, carbon aerogel powder, graphene oxide, carbon nanotubes, C 60 One or more of ethylene.

[0011] In the above scheme, when the low thermal conductivity powder is a carbon material such as nano carbon black, the obtained product is a carbon-based flexible nanoporous thermal insulation material. This material has broad application prospects in the fields of wave absorption and heat insulation in the end cap of hypersonic weapons, ultra-high temperature thermal protection systems of advanced weapon systems, etc.

[0012] In the present invention, the fiberizable adhesive is selected from one or more of polytetrafluoroethylene, copolymer of ethylene and tetrafluoroethylene, copolymer of hexafluoropropylene and tetrafluoroethylene. In some embodiments of the present invention, the fiberizable adhesive is polytetrafluoroethylene.

[0013] In order to further improve the performance of the flexible nano thermal insulation material, the formula includes additives. The additives include one or more of an infrared sunscreen, a short inorganic fiber or whisker for reinforcement. The mass proportion of the infrared sunscreen is 1% to 5%, and the mass proportion of the short inorganic fiber or whisker for reinforcement is 1% to 5%. The addition of an infrared sunscreen can suppress high-temperature infrared radiation and thus reduce the thermal conductivity, while the addition of short inorganic fibers or whiskers for reinforcement can improve the dimensional stability of the material at high temperatures.

[0014] Specifically, the infrared sunscreen is selected from one or more of silicon carbide powder, rutile titanium dioxide, anatase titanium dioxide, boron carbide powder, zirconium oxide powder, zircon powder and the like.

[0015] Furthermore, when the flexible nano thermal insulation material is used in high temperature scenarios, the particle size of the infrared sunscreen agent has certain requirements. The specific design can be based on the following rules: According to Wien's displacement law, the wavelength λ at which the energy density of infrared rays radiated outward by a high-temperature black body or gray body heat source is at its maximum value * and the heat source temperature T satisfies (λ * / m)×(T / K)=b=0.002897. The particle size of infrared shading agent should be slightly larger than λ according to D50 * (T) When the particle size of the infrared sunscreen agent is too small (such as <1μm), the infrared radiation from the heat source directly penetrates the heat insulation layer and cannot shield the infrared heat radiation.

[0016] The chopped inorganic fibers or whiskers for reinforcement are selected from one or more of chopped glass fibers, aluminum silicate fibers, brucite fibers, sepiolite fibers, aluminum silicate whiskers, and the like.

[0017] In the preparation method of the present invention, the rotation speed and time of the ball milling step need to be adjusted according to the raw material ratio. The rotation speed needs to ensure that the fiberizable adhesive is fully sheared and stretched but not excessively fiberized and cannot be further processed. Otherwise, the obtained product will have many through cracks in the thickness direction and the thermal insulation effect is poor.

[0018] In some embodiments of the present invention, the ball milling speed is 300-500 rpm, and the time is 10-15 minutes. Further, the ball milling process uses a 5 mm diameter agate ball, the ball and the material are put in at a mass ratio of 5:1, the filling volume of the silo is 50%-70%, and after mixing at 300-500 rpm for 10-15 minutes, the powder is sieved out with a 20-mesh screen and the powder is collected.

[0019] In some embodiments of the present invention, the rolling adopts a multi-stage double-roller system, and the roller spacing of each stage of rollers decreases according to a certain roller spacing d, and the value range of d is 0.1~0.8mm, preferably 0.5mm. The double rollers at each stage are arranged symmetrically along a center line, and the rollers at each stage have the same roller length and linear speed. During the rolling process, it is necessary to go through multiple stages and multiple rolling so that the fiberizable adhesive can be fully sheared and stretched to form slender fibers, which has a binding effect on the powder in the mixture. At the same time, the pre-designed product parameters (such as density, thickness, etc.) should also be considered. In some embodiments, when the low thermal conductivity powder uses a hydrophilic fumed silica powder, because its surface is rich in hydroxyl groups, the intermolecular hydrogen bonds will further enhance the adhesion of the powder.

[0020] In a second aspect, the present invention provides a flexible nano thermal insulation material prepared by the above preparation method.

[0021] According to the flexible nano thermal insulation material provided by the present invention, the density of the flexible nano thermal insulation material is 150-400 mg / cm 3 The apparent thermal conductivity at room temperature is 20 to 50 mW / (m·K).

[0022] The flexible nano thermal insulation material provided by the present invention has the porous structure of the low thermal conductivity powder itself and the pore structure formed by the accumulation of solid raw material particles, and the average pore diameter is 16-20nm.

[0023] In a third aspect, the present invention provides the application of the above-mentioned flexible nano thermal insulation material in the field of thermal insulation and heat preservation.

[0024] Since the flexible nano thermal insulation material prepared by the present invention has excellent flexibility, thermal insulation performance and certain tensile and compressive properties, it can be used as a thermal insulation and heat preservation material and is widely used in aerospace, construction engineering, shipbuilding, automobile manufacturing, industrial production and other fields.

[0025] In a fourth aspect, the present invention further provides a flexible nano thermal insulation felt, the raw materials of which include low thermal conductivity powder, a fiberizable adhesive, a hydrated salt phase change material, a low temperature melting glass powder and optional additives.

[0026] Preferably, the additives include one or more of an infrared shading agent, chopped inorganic fibers or whiskers for reinforcement, and carbonates.

[0027] More preferably, the raw materials of the flexible nano insulation felt include, by mass percentage, 60-65% low thermal conductivity powder, 1-10% fiberizable adhesive, 15-25% hydrated salt phase change material, 1-5% low-temperature melting glass powder, 1-5% infrared sunshade, 1-5% chopped inorganic fibers or whiskers for reinforcement, and 1-5% carbonate.

[0028] The hydrated salt phase change material can be selected from nano magnesium hydroxide powder, nano aluminum hydroxide powder, sepiolite fiber powder, brucite fiber powder, Na2B4O7·10H2O, Na2B4O7·5H2O, aluminum dihydrogen tripolyphosphate (AlH2P3O 10 ·2H2O) in one or more.

[0029] The low-temperature melting glass powder may be a bismuth-based glass powder or a high-alkali glass powder.

[0030] The purpose of designing the above components is that in high-temperature application scenarios, after the fiberizable adhesive in the flexible nano-insulation felt is completely decomposed, the low-temperature melting glass powder or hydrated salt phase change material can continue to play a bonding role at high temperature, so that the insulation felt still has sufficient mechanical properties when the operating temperature is ≥500℃, and it can be ceramicized at higher temperatures (≥800℃) to play a role in blocking flames.

[0031] Furthermore, the carbonate is a carbonate powder that undergoes an endothermic decomposition chemical reaction at high temperature and releases flame-retardant CO2 gas, such as nano Li2CO3, Na2CO3, CaCO3, etc.

[0032] Among them, the selection range of low thermal conductivity powder, fiberizable adhesive, infrared shading agent, and chopped inorganic fibers or whiskers for reinforcement is the same as described above.

[0033] That is, the low thermal conductivity powder is selected from fumed silica powder, silica aerogel powder, alumina aerogel powder, zirconia aerogel powder, vermiculite powder, perlite powder, nano carbon black, graphene oxide, carbon nanotubes, carbon aerogel powder, C 60 One or more of ethylene.

[0034] The fiberizable adhesive is selected from one or more of polytetrafluoroethylene, copolymer of ethylene and tetrafluoroethylene, copolymer of hexafluoropropylene and tetrafluoroethylene. In some embodiments of the present invention, the fiberizable adhesive is polytetrafluoroethylene.

[0035] The infrared sunscreen is selected from one or more of silicon carbide powder, rutile titanium dioxide, anatase titanium dioxide, boron carbide powder, zirconium oxide powder, zircon powder and the like.

[0036] The chopped inorganic fibers or whiskers for reinforcement are selected from one or more of chopped glass fibers, aluminum silicate fibers, brucite fibers, sepiolite fibers, aluminum silicate whiskers, and the like.

[0037] The present invention also provides a method for preparing the above-mentioned flexible nano thermal insulation felt, comprising: evenly mixing raw materials except the fiberizable adhesive, mixing the obtained material with the fiberizable adhesive and ball milling to obtain flocs, kneading the flocs and then rolling them to obtain the flexible nano thermal insulation felt.

[0038] The internal mixing process is carried out by using a rubber internal mixer, and the internal mixing parameters are 10-30 rpm for 5-10 minutes. The internal mixing process is used in the above scheme to knead the loose flakes into a mass.

[0039] Furthermore, the present invention can also prepare multi-layer nano-flexible thermal insulation felt.

[0040] Specifically, the flexible nano-insulating material or flexible nano-insulating felt of the present invention, an infrared reflective screen (copper-plated polyimide film, gold-plated polyimide film, aluminum foil, stainless steel foil, etc.) and / or a long fiber woven mesh cloth that plays a mechanical reinforcement role (quartz fiber mesh cloth, glass fiber mesh cloth, basalt fiber mesh cloth, ramie fiber mesh cloth, flax fiber mesh cloth, bamboo fiber mesh cloth, reed fiber mesh cloth, etc.) are alternately laid layer by layer, the outermost layer uses high-temperature resistant ceramic fiber fabric or high-temperature alloy fiber fabric, and is quilted using high-temperature resistant ceramic fiber sewing thread, and finally a thermal control coating / fireproof coating and an anti-icing and anti-oil coating are sprayed on the outermost layer of the product to obtain a multi-layer nano-flexible insulation felt product.

[0041] This type of product has broad application prospects in the fields of satellite thermal protection, auxiliary power units of aerospace vehicles, flight or key data recorders, thermal management of bleed air and deicing pipes, and detachable insulation covers for industrial equipment.

[0042] In a fifth aspect, as an application of the flexible nano thermal insulation material, the present invention provides a fireproof thermal insulation gasket between battery cells, which uses the above-mentioned flexible nano thermal insulation material as the core material.

[0043] Specifically, a flexible nano thermal insulation material is used as the core material, and a PET film or a PI film is used for vacuum hot pressing packaging to obtain a fireproof thermal insulation gasket between power / energy storage battery cells.

[0044] Typical gasket density is 0.33±0.02g / cm 3 For the application scenarios of fireproof and heat-insulating gaskets for power batteries, the mainstream thickness requirements for fireproof and heat-insulating gaskets between power battery cells are 1mm and 2mm.

[0045] In a sixth aspect, as an application of the flexible nano thermal insulation material, the present invention provides a thermal insulation pipe shell, which uses the above-mentioned flexible nano thermal insulation material as an interlayer between an inner pipe and an outer pipe.

[0046] Specifically, a multi-layer flexible nano-insulation material shell can be wound between two parallel steel pipes to manufacture an insulated pipeline for offshore crude oil transportation.

[0047] In a seventh aspect, as an application of the flexible nano thermal insulation material, the present invention provides a vacuum insulation panel, which uses the above-mentioned flexible nano thermal insulation material as a core material.

[0048] Specifically, the above-mentioned flexible nano-insulation material of the present invention can be used in combination with a getter and a vacuum hot pressing packaging process to obtain a vacuum insulation board with a room temperature thermal conductivity as low as 0.004W / (m·K), which has broad application prospects in the fields of ultra-thin energy-saving refrigerators, cold chain logistics carriage panels, outdoor communications, and thermal insulation interlayers of power cabinets.

[0049] The present invention provides a flexible nano thermal insulation material and a preparation method and application thereof, wherein low thermal conductivity powder is cross-linked and fixed by rolling with original fibers formed by a fibrillating adhesive to form a flexible film, thereby maintaining the pore structure of the low thermal conductivity powder itself without introducing a high thermal conductivity adhesive for molding, thereby retaining the low thermal conductivity of the powder itself while having good processing and molding properties. The flexible nano thermal insulation material prepared by the present invention has excellent flexibility, thermal insulation performance and certain tensile and compressive properties, and can be widely used in aerospace, construction engineering, shipbuilding, automobile manufacturing and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 Schematic diagram of a multi-stage double-roll system of a roller press used in the preparation process of an embodiment of the present invention.

[0051] Figure 2 This is a microstructure diagram of the flexible nano thermal insulation material provided in Example 2 of the present invention.

[0052] Figure 3 This is the hot stage test result of Example 6 of the present invention, with a front surface temperature of 1100° C. and a sample thickness of 30 mm.

[0053] Figure 4 It is a microstructure diagram of the material provided in Comparative Example 1 of the present invention.

[0054] Figure 5 It is a microstructure diagram of the material provided in Comparative Example 2 of the present invention.

[0055] Figure 6 It is a microstructure diagram of the material provided in Comparative Example 4 of the present invention.

[0056] Figure 7 These are the hot stage test results of Example 4 and Comparative Example 6 of the present invention, and the sample sizes are all 100 mm×100 mm×2 mm.

[0057] Figure 8 These are the apparent thermal conductivity measurement results of the flexible nano-insulating materials provided in different embodiments. The room temperature apparent thermal conductivity test standard is GB / T 10295-2008, and the high temperature thermal conductivity test standard is GJB 10252-2021. DETAILED DESCRIPTION

[0058] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0059] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels.

[0060] In the following examples, the PTFE used is Chemours 601X polytetrafluoroethylene produced by DuPont.

[0061] The silicon carbide powder used was produced by Beijing Micro-Nano Ultrafine Materials Co., Ltd., W-3.5 type, α phase, D50 = 3.5 μm.

[0062] The fumed silica powder used was Wacker N20 with a specific surface area of ​​200 m 2 / g, hydrophilic type.

[0063] The chopped glass fibers used were 4-6 mm in length and 5-7 μm in diameter and were produced by Jushi, China.

[0064] The high shear mixer used was Cyclomix®, produced by Hosokawa Micron Co., Ltd., Japan.

[0065] The ball mill used was a WGM-500L ball mill produced by Wuxi Xinyang Equipment Technology Co., Ltd.

[0066] The roller press used in the following embodiments is a multi-stage double-roller system, the roller spacing of each stage of rollers decreases by 0.5 mm, the double rollers of each stage are arranged symmetrically along a center line, and the rollers of each stage have the same roller length and linear speed. The structural schematic diagram is shown in FIG. Figure 1 shown.

[0067] Example 1

[0068] This embodiment provides a flexible nano thermal insulation material, and the preparation method thereof is as follows: The silica aerogel powder and PTFE were mixed at a mass ratio of 95:5, and the flocculent mixture was extruded in a roller press after ball milling at 300 rpm for 8 minutes. The density of the mixture was 200 mg / cm 3 The apparent thermal conductivity of the thin film material at room temperature is 18 mW / (m·K).

[0069] Example 2

[0070] This embodiment provides a flexible nano thermal insulation material, and the preparation method thereof is as follows: Fumed silica powder and PTFE were mixed at a mass ratio of 95:5, and the flocculent mixture was extruded in a roller press after ball milling at 300 rpm for 8 minutes. The density of the mixture was 350 mg / cm 3 The apparent thermal conductivity of the thin film material at room temperature is 20 mW / (m·K).

[0071] Figure 2 This is a microstructure diagram of the flexible nano thermal insulation material provided in Example 2.

[0072] Example 3

[0073] This embodiment provides a flexible nano thermal insulation material, and the preparation method thereof is as follows: Fumed silica powder, silicon carbide powder and PTFE were mixed in a mass ratio of 90:5:5, ball-milled at 300 rpm for 8 minutes, and then the flocculent mixture was extruded in a roller press to obtain a density of 350 mg / cm 3 The apparent thermal conductivity of the thin film material at room temperature is 20 mW / (m·K).

[0074] Example 4

[0075] This embodiment provides a flexible nano thermal insulation material, and the preparation method thereof is as follows: Fumed silica powder, titanium dioxide powder (particle size greater than 1 μm) and PTFE were mixed in a mass ratio of 90:5:5, ball-milled at 300 rpm for 8 minutes, and the flocculent mixture was extruded in a roller press to obtain a density of 350 mg / cm 3 The apparent thermal conductivity of the thin film material at room temperature is 22 mW / (m·K).

[0076] Example 5

[0077] This embodiment provides a flexible nano thermal insulation material, and the preparation method thereof is as follows: Take fumed silica powder, chopped glass fiber, silicon carbide powder and PTFE in a mass ratio of 89:3:3:5, put the fumed silica powder, chopped glass fiber and silicon carbide powder into a high shear mixer hopper, stir and mix at 800 rpm for 30 minutes to fully mix, then add PTFE and ball mill at 300 rpm for 10 minutes, extrude the obtained flocculent mixture in a roller press, and obtain a density of 350 mg / cm by roller pressing. 3 The apparent thermal conductivity of the thin film material at room temperature is 20mW / (m·K).

[0078] Example 6

[0079] This embodiment provides a flexible nano thermal insulation felt, the formula of which is as follows: Fumed silica powder (62%); chopped glass fiber (3%); sepiolite fiber powder (5%); brucite fiber powder (5%); lithium carbonate (5%); borax decahydrate (5%); aluminum dihydrogen tripolyphosphate (5%); Beijing Tianlichuang Glass Technology Co., Ltd. SE-925 bismuth-containing glass powder (1%); Beijing Tianlichuang Glass Technology Co., Ltd. SE905 high-alkali glass powder (1%); silicon carbide powder (3%); PTFE (5%).

[0080] The preparation method is as follows: First, the materials except PTFE were placed in the silo of the high shear mixer and stirred at 800 rpm for 30 minutes to fully mix. Then, the obtained materials and PTFE were ball-milled at 300 rpm for 10 minutes to form a flocculent mixture, which was then placed in a rubber mixer and kneaded at 20 rpm for 5 minutes to obtain a second agglomerated mixture. Under the action of multi-stage roller pressing, a density of 300 mg / cm 3 of film material.

[0081] The flexible nano thermal insulation felt prepared in this embodiment has an obvious constant temperature platform between 100 and 150°C in the thermal insulation performance test of the hot stage. Figure 3 As shown, this is a typical feature of hydrated salt phase change materials losing crystal water.

[0082] Example 7

[0083] This embodiment provides a carbon-based flexible nano thermal insulation felt, and its formula is as follows: Nano carbon black (89%), Jiangxi Black Cat Carbon Black Co., Ltd., HMQ-C10; chopped carbon fiber (3%), chopped length 4~6mm, Zhongfu Shenying SYT50S, the carbon fiber is subjected to surface sizing agent removal according to the method published in Chinese invention patent application No. 202410776310.6; silicon carbide powder (3%); PTFE (5%).

[0084] The preparation method is as follows: First, the materials except PTFE were placed in the silo of the high shear mixer and stirred at 800 rpm for 30 minutes to fully mix. Then, the obtained materials and PTFE were ball-milled at 300 rpm for 10 minutes to form a flocculent mixture, which was then placed in a rubber mixer and kneaded at 20 rpm for 5 minutes to obtain a second agglomerated mixture. Under the action of multi-stage roller pressing, a density of 300 mg / cm 3 The film material has good flexibility, heat insulation and electromagnetic wave absorption properties.

[0085] Example 8

[0086] This embodiment provides a flexible nano thermal insulation felt, the formula of which is as follows: Fumed alumina powder (65%); sepiolite fiber powder (5%); brucite fiber powder (5%); lithium carbonate (5%); borax decahydrate (5%); aluminum dihydrogen tripolyphosphate (5%); Beijing Tianlichuang Glass Technology Co., Ltd. SE-925 bismuth-containing glass powder (1%); Beijing Tianlichuang Glass Technology Co., Ltd. SE-905 high-alkali glass powder (1%); silicon carbide powder (3%); PTFE (5%).

[0087] The preparation method is as follows: First, the materials except PTFE adhesive were placed in the silo of the high shear mixer and stirred at 800 rpm for 30 minutes to fully mix. Then, the first mixture was mixed with PTFE, and ball milled at 300 rpm for 10 minutes to form a flocculent mixture. The mixture was placed in a rubber mixer and kneaded at 20 rpm for 5 minutes to obtain a second agglomerated mixture. The agglomerated second mixture was formed under the action of multi-stage roller pressing to form a density of 300 mg / cm 3 of film material.

[0088] Comparative Example 1

[0089] This comparative example provides a porous film material, which differs from Example 2 in that the ball milling time is extended to 15 minutes.

[0090] As a result, due to the long ball milling time, the obtained product has many through-cracks in the thickness direction, such as Figure 4 As shown, the product has poor thermal insulation effect and the apparent thermal conductivity at room temperature is 57 mW / (m·K).

[0091] Comparative Example 2

[0092] This comparative example provides a porous film material, which differs from Example 2 in that the ball milling speed is increased to 800 rpm.

[0093] As a result, due to the high ball milling speed, the obtained product has many through-cracks in the thickness direction, such as Figure 5 As shown, the product has poor thermal insulation effect and the apparent thermal conductivity at room temperature is 53 mW / (m·K).

[0094] Comparative Example 3

[0095] This comparative example provides a porous film material, which differs from Example 2 in that, in the multi-stage rolling system, the gap feed amount between the stages is 1 mm / stage.

[0096] As a result, due to the excessive feed amount between the inter-stage roller gaps, a large number of through-cracks appeared in the thickness direction of the obtained product, and the product became waste.

[0097] Comparative Example 4

[0098] This comparative example provides a porous film material, which differs from Example 1 in that the PTFE content is increased to 15%, that is, the fumed silica powder and PTFE are mixed in a mass ratio of 85:15, and the subsequent steps are the same as Example 1.

[0099] As a result, due to the excessive PTFE content, part of the PTFE is difficult to be completely drawn into fibers under the action of shear force, but agglomerates into blocks to block the pore structure, such as Figure 6 As shown, the obtained product has poor thermal insulation effect, and the apparent thermal conductivity at room temperature is 61 mW / (m·K).

[0100] Comparative Example 5

[0101] This comparative example provides a porous film material, which differs from Example 3 in that the content of the infrared shading agent SiC is increased to 10%, that is, the gas-phase silica powder, silicon carbide powder and PTFE are mixed in a mass ratio of 85:10:5, and the subsequent steps are the same as Example 3.

[0102] As a result, the thermal insulation performance of the obtained product decreases because the apparent density of the product increases and the solid phase heat conduction increases significantly.

[0103] Comparative Example 6

[0104] This comparative example provides a porous film material, which differs from Example 4 in that the sunscreen uses nano-TiO2 powder with a particle size of 300 nm.

[0105] As a result, the obtained product has no shading effect. The hot stage test results show that when 600℃ is applied to one side, the back temperature of the obtained product reaches 330℃, which is significantly higher than the sample made of micron-sized TiO2 powder. Figure 7 shown.

[0106] Comparative Example 7

[0107] In Example 3, when SiC with D50=30μm is used as the sunscreen, the thermal insulation performance decreases. The reason is that compared with SiC with D50=3.5μm, when the added amount is only 5% by mass, the large-particle sunscreen cannot completely cover the entire plane, and there is a light leakage area. If the amount of SiC is increased, the solid-phase heat conduction will increase significantly.

[0108] Table 1 shows the thermal conductivity of various insulation materials in W / (m·K). The room temperature thermal conductivity test standard is GB / T 10295-2008, and the high temperature thermal conductivity test standard is GJB 10252-2021. Figure 8 This is a graph of the apparent thermal conductivity of different insulation materials in Table 1.

[0109] Table 1

[0110] Application example 1: Preparation of VIP board

[0111] The film obtained in Example 6 was placed in a VIP packaging bag, and a getter bag was placed in it. The vacuum device was turned on and the vacuum was continuously drawn for 72 hours. The vacuum needle was then removed and hot-pressed at 110°C to obtain a VIP board with an apparent thermal conductivity of 4 mW / (m·K) at room temperature.

[0112] Application example 2: Sewing multiple layers of thermal insulation felt

[0113] A multi-layer nano-flexible thermal insulation felt is prepared by alternately laying the flexible nano-insulating material of the present invention, an infrared reflective screen (copper-plated polyimide film, gold-plated polyimide film, aluminum foil, stainless steel foil, etc.) and a quartz fiber mesh cloth that plays a mechanical reinforcement role layer by layer, using a high-temperature resistant alumina ceramic fiber fabric or a high-temperature alloy fiber fabric as the outermost layer, and quilting with a high-temperature resistant ceramic fiber sewing thread, and finally spraying a thermal control coating on the outermost layer of the product to obtain a multi-layer nano-flexible thermal insulation felt product.

[0114] It should be noted that the endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed in this article.

[0115] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "specific implementation methods", or "some specific implementation methods" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a flexible nano thermal insulation material, characterized in that: include: The low thermal conductivity powder, the fiberizable adhesive and the optional additives are mixed, ball-milled to obtain flocs, and then the flocs are rolled to form the flexible nano thermal insulation material in the form of a film.

2. The method for preparing the flexible nano thermal insulation material according to claim 1, characterized in that: The mass proportion of the low thermal conductivity powder is 85% to 95%, and the mass proportion of the fiberizable adhesive is 1% to 10%.

3. The method for preparing the flexible nano thermal insulation material according to claim 2, characterized in that: The low thermal conductivity powder is selected from fumed silica powder, silica aerogel powder, alumina aerogel powder, zirconia aerogel powder, vermiculite powder, perlite powder, nano carbon black, carbon aerogel powder, graphene oxide, carbon nanotubes, C 60 One or more of succotene; The fiberizable adhesive is selected from one or more of polytetrafluoroethylene, copolymer of ethylene and tetrafluoroethylene, and copolymer of hexafluoropropylene and tetrafluoroethylene.

4. The method for preparing the flexible nano thermal insulation material according to claim 1, characterized in that: The additives include one or more of an infrared sunscreen agent, and short-cut inorganic fibers or whiskers for reinforcement; the mass proportion of the infrared sunscreen agent is 1% to 5%, and the mass proportion of the short-cut inorganic fibers or whiskers for reinforcement is 1% to 5%.

5. The method for preparing the flexible nano thermal insulation material according to claim 1, characterized in that: The ball mill has a rotation speed of 300-500 rpm and a time of 10-15 minutes.

6. The method for preparing the flexible nano thermal insulation material according to claim 1, characterized in that: The rolling process adopts a multi-stage double-roller system, the roller spacing of each stage of rollers decreases by 0.1-0.8 mm, the double rollers of each stage are symmetrically arranged along a center line, and the rollers of each stage have the same roller length and line speed.

7. A flexible nano thermal insulation material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.

8. The flexible nano thermal insulation material according to claim 7, characterized in that: The density of the flexible nano thermal insulation material is 150-400 mg / cm 3 The apparent thermal conductivity at room temperature is 20 to 50 mW / (m·K).

9. The flexible nano thermal insulation material according to claim 7, characterized in that: The flexible nano thermal insulation material has the porous structure of the low thermal conductivity powder itself and the pore structure formed by the accumulation of solid raw material particles, and the average pore diameter is 16-20nm.

10. Use of the flexible nano thermal insulation material according to any one of claims 7 to 9 in the field of thermal insulation and heat preservation.

11. A flexible nano thermal insulation felt, characterized in that: The raw materials include low thermal conductivity powder, fiberizable adhesive, hydrated salt phase change material, low temperature melting glass powder and optional additives; Preferably, the additive includes one or more of an infrared sunscreen, chopped inorganic fibers or whiskers for reinforcement, and carbonates; More preferably, the raw materials of the flexible nano insulation felt include, by mass percentage, 60-65% low thermal conductivity powder, 1-10% fiberizable adhesive, 15-25% hydrated salt phase change material, 1-5% low-temperature melting glass powder, 1-5% infrared sunshade, 1-5% chopped inorganic fibers or whiskers for reinforcement, and 1-5% carbonate.

12. The method for preparing the flexible nano thermal insulation felt according to claim 11, characterized in that: include: After the raw materials except the fiberizable adhesive are uniformly mixed, the obtained materials are mixed with the fiberizable adhesive and ball-milled to obtain floccules, and the floccules are kneaded and then rolled to obtain the flexible nano thermal insulation felt.

13. A fireproof and heat-insulating gasket between battery cells, characterized in that: The flexible nano thermal insulation material according to any one of claims 7 to 9 is used as the core material.

14. A thermal insulation pipe shell, characterized in that: The flexible nano thermal insulation material according to any one of claims 7 to 9 is used as an interlayer placed between the inner tube and the outer tube.

15. A vacuum insulation panel, characterized in that: The flexible nano thermal insulation material according to any one of claims 7 to 9 is used as the core material.

Citation Information

Patent Citations

  • Microporous insulators

    CN108475748A

  • Inorganic nanopowder compound thermal insulation felt and preparation method thereof

    CN110645445A

  • Electronic-grade flexible polytetrafluoroethylene heat insulation film and preparation method thereof

    CN114132034A

  • Aerogel / ptfe composite insulating material

    CN1875060A

  • Insulator with high thermal conductivity

    US4563488A

Cited By

  • Ultra-thin honeycomb reinforced nano heat insulation gasket as well as preparation method and application thereof

    CN120484500A

  • An ultrathin honeycomb reinforced nanometer adiabatic gasket, a preparation method and application thereof

    CN120484500B

  • Phenolic hybrid SiO2 mesoporous microsphere and application thereof

    CN120923959A